Prevalence of Gastro-Intestinal Parasites of Rhesus Macaque (Macaca Mulatta Zimmermann, 1780) and Hanuman Langur (Semnopithecus Entellus Dufresne, 1797) In Devghat, Chitwan, Nepal - Adhikari, Pujan Prasad; Dhakal, Pitambar (Journal of Institute of Science and Technology, 2018)
The present investigation was undertaken to study the prevalence of gastrointestinal parasites in Rhesus Macaque and Hanuman Langur at Devghat, Chitwan. Altogether 93 fresh faecal samples were collected from Rhesus Macaque belonging to five troops and Hanuman Langur of two troops. About 10 gm of faecal material was collected in sterile vials with 2.5% potassium dichromate solution. These samples were examined microscopically by faecal concentration methods viz. floatation technique and sedimentation technique. Out of 93 samples, 69 (74.20%) were found positive for at least one parasite. Prevalence of helminth and protozoan parasites was 52.68% and 40.86% respectively. Altogether, 10 species of parasites including seven helminth and three protozoa were identified based on morphological characteristics of their eggs and cysts under light microscopy. The most commonly detected parasites were Balantidium coli (27.95%) followed by Eimeria sp. (16.12%), Entamoeba sp. (13.97%), Trichuris sp. (23.65%), Ascaris sp. (11.82%), Strongyloides sp. (10.75%), Oesophagostomum sp. (5.37%), Hookworm sp. (3.22%), Trichostrongylus sp. (3.22%) and Hymenolepis sp. (1.07%). Unidentified larvae of nematode which account for 6.45% of total samples were also recorded. Single, double, triple and multiple species of parasites were found in 36.55%, 29.03%, 6.45% and 2.15% samples respectively. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 12-18